1/7 Bondel road : an endearing short story collection - Gautam Benegal (New Delhi : Wisdom Tree, 2011)
1/7 Bondel Road is about moments some bewitching, some frozen, some crisp, others lingering, still others haunting and about the people who help frame them as memories. Ten vividly sketched endearing vignettes of those growing up years in a quintessential Calcutta lane, create a gentle universe filled with impressions that last a lifetime. A sharply observant set of stories, that end with inevitably poignant, unexpected turns that give old truths new meaning.
Keywords: Fiction; Short Stories